Can the Concepts of Energy and Psychological Energy Enrich Our Understanding of Psychosocial Adaptation to Traumatic Experiences, Chronic Illnesses and Disabilities? - Livneh, Hanoch (Frontiers in Psychology, 2022)
The aim of this paper is to familiarize the reader with the concept of psychological energy (PE), and the role it plays in deepening our understanding of psychosocial adaptation to traumatic life events and, more pointedly, the onset of chronic illness and disability (CID). In order to implement this aim, the author has undertaken the following steps: First, a brief historical review of the nature of energy, force and action, as traditionally conceived in the field of physics, is provided. Second, an overview of PE is presented, with a shared emphasis on both its historical underpinnings and its present conceptualizations in the fields of social, health and rehabilitation psychology. Particular emphasis is placed upon applications of PE in the domains of adaptation to stress, trauma and CID onset. Third, the author reviews the measuring instruments that have been traditionally applied to the assessment of the nature, content and magnitude of PE and its dynamics. Finally, new perspectives are offered on the dimensional structure, processes and dynamics, assumed to undergird PE, its underlying conceptual similarities to physical energy, and its potential and deeper link to the process of psychosocial adaptation in the aftermath of experiencing trauma and the onset of CID.